Rapid and sensitive pollutant detection by induction of heat shock gene-bioluminescence gene fusions. - Van Dyk, T K (1994)
Heat shock gene expression is induced by a variety of environmental stresses, including the presence of many chemicals. To address the utility of this response for pollutant detection, two Escherichia coli heat shock promoters, dnaK and grpE, were fused to the lux genes of Vibrio fischeri. Metals, solvents, crop protection chemicals, and other organic molecules rapidly induced light production from E. coli strains containing these plasmid-borne fusions. Introduction of an outer membrane mutation, tolC, enhanced detection of a hydrophobic molecule, pentachlorophenol. The maximal response to pentachlorophenol in the tolC+ strain was at 38 ppm, while the maximal response in an otherwise isogenic tolC mutant was at 1.2 ppm. Stress responses were observed in both batch and chemostat cultures. It is suggested that biosensors constructed in this manner may have potential for environmental monitoring.